Pendidikan Diniyah Formal : a Formal Curriculum for Pesantren in Indonesia - Syukron, Ahmad; Samsudi, Samsudi; Kustiono, Kustiono (Innovative Journal of Curriculum and Educational Technology, 2020)
Starting from 2015, the ministry of religions and affairs of Indonesia has developed a type of formal education service, specially for pesantren by announcing Pendidikan Diniyah Formal (PDF). Some pesantren in Indonesia have implemented this kind of curriculum, so that it is necessary to conduct a study related to its implementation in order to acquire the whole description of its actualization in pesantren. This study aims to describe the implementation of PDF at APIK (Asrama Pendidikan Islam Kaliwungu), one of pesantren in Kaliwungu. This study belongs to case study and uses qualitative approach. The data were collected through interview, observation, and documentation in order to know the planning, implementation, and evaluation process of PDF. This study uses the model of Miles and Huberman which includes data reduction, data display, and conclusion drawing in analyzing the data. The research result shows the implementation of PDF at APIK including its learning objectives, materials, sources, time allotment, as well as the evaluation system has been appropriate with the basic rule of PDF established by the government. However, it still remains the specific characteristics of pesantren, including its local content, classroom management, as well as the learning strategy used such as bandongan and sorogan. The result of this study can be used as reference for other pesantren applying PDF and to facilitate some pesantren which have applied PDF in spreading its existence among Indonesian people, so that their graduates can be accepted in higher education institution as well as other formal institutions.